Media facades : history, technology, content. - Haeusler, Matthias Hank, ....- (Ludwigsburg : Avedition, 2009)
The book introduces a canon of media architectural terminology and shows the history of media facades through early examples of embedding media in architecture, like Times Square and Centre Pompidou. State-of-the-art developments are presented with approx. 30 international projects of contemporary media architecture separated and classified in seven different technical categories: projection facades, rear projection facades, window raster animation, display facades, illuminated facades, mechanical facades and voxel facades. Each of these categories is introduced by explaining the technology and presenting built examples. The book is rounded off by an analysis of the representational characteristics of media facades and an introduction of possible forms of content.
Keywords: Architectuur